Generative Learning Strategies to Improve Students’ Cognitive Engagement in Online Classes at Islamic School: A Systematic Review - Arief Ardiansyah; Bagus Cahyanto (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to reveal generative learning strategies for increasing students' cognitive involvement. Design/methods/approach – This systematic review research was carried out using seven stages. The stages include formulating research questions, determining the type of research, conducting a comprehensive literature search, filtering literature search results, assessing research that meets the criteria, synthesizing research, and assessing heterogeneity between studies. Findings – This research shows how the learning process occurs in individuals based on generative learning theory. The generative learning strategies include learning through summarizing, learning through mapping, learning through drawing, learning through imagination, and learning through teaching. Research Implications/Limitations – These findings can be used as a reference for teachers in implementing learning strategies that can involve students' cognitive aspects to produce more meaningful learning achievements. Originality/value – These findings provide educators with insight into the information processing occurring in a person's cognition and reveal several learning strategies that align with information processing theory